Repurposing of Medicines in the EU: Launch of a Pilot Framework - Asker-Hagelberg, Charlotte; Boran, Tomas; Bouygues, Christelle; Eskola, Sini Marika; Helmle, Laszlo; Hernández, César; Houýez, François; Lee, Helen; Lingri, Dimitra D.; Louette, Laurent; Meheus, Lydie; Penninckx, Wim; et al. (Frontiers in Medicine, 2022)
Repurposing of authorised medicines has been under discussion for a long time. Drug repurposing is the process of identifying a new use for an existing medicine in an indication outside the scope of the original approved indication. Indeed, COVID-19 health crisis has brought it to the frontline by proving the usefulness of this practice in favour of patients for an early access to treatment. Under the umbrella of the Pharmaceutical Committee and as a result of the discussions at the European Commission Expert Group on Safe and Timely Access to Medicines for Patients (STAMP) a virtual Repurposing Observatory Group (RepOG) was set up in 2019 to define and test the practical aspects of a pilot project thought to provide support to ‘not-for-profit’ stakeholders generating or gathering data for a new therapeutic use for an authorised medicine. The group’s initial plan was impacted by the outbreak of the SARS-CoV-2 pandemic and the launch of the pilot needed to be postponed. This article describes the progress and the activities conducted by the group during this past and yet extraordinary 2020-2021 to keep the project alive and explores on the background of this topic together with the obvious opportunities this health crisis has brought up in terms of repurposing of medicines.